Implementation of non-communicable disease policies: a geopolitical analysis of 151 countries - Allen, LN; Nicholson, BD; Yeung, BYT; Goiana-Da-Silva, F (Elsevier, 2019)
Background Most countries have endorsed WHO non-communicable disease (NCD) best buy policies, but we know very little about global implementation patterns and about the geopolitical factors affecting implementation. We aimed to assess global implementation based on analysis of multiple geopolitical datasets. Methods We used the 2015 and 2017 WHO NCD progress monitor reports to calculate aggregate implementation scores for 151 countries, based on their implementation of 18 WHO-recommended NCD policies. We ranked all countries and used descriptive statistics to analyse global trends. We used linear regression to assess the associations between policy implementation and World Bank geographic region, risk of premature NCD mortality, percentage of all deaths caused by NCDs, World Bank income group, human capital index, democracy index, and tax burden. Findings In 2017, the mean NCD policy implementation score was 49·3% (SD 18·4%). Costa Rica and Iran had the joint-highest implementation scores (86·1% of all WHO-recommended policies). Scores were lowest in Haiti and South Sudan (5·5%). Between 2015 and 2017, aggregate implementation scores rose in 109 countries and regressed in 32 countries. Mean implementation rose for all of the 18 policies except for those targeting alcohol and physical activity. The most commonly implemented policies were clinical guidelines, graphic warnings on tobacco packaging, and NCD risk factor surveys. Our multiple linear regression model explained 61·1% of the variance in 2017 aggregate scores (p<0·0001), but we found evidence of a high degree of collinearity between the explanatory variables. Interpretation Implementation of WHO-recommended NCD policies is increasing over time. On average, countries implemented just under half of the NCD policies recommended by WHO in 2017. Nutrition-related policies saw gains, while those related to alcohol and physical activity were the most likely to have been dropped. Aggregate implementation scores tended to be highest in high-income countries that invest in health care and education. Funding National Institute for Health Research, Imperial College London, University of Oxford.